1996
DOI: 10.1007/bf00192434
|View full text |Cite
|
Sign up to set email alerts
|

Expression of antigens related to apoptosis and cell proliferation in chronic nonsuppurative destructive cholangitis in primary biliary cirrhosis

Abstract: The initial injury in primary biliary cirrhosis (PBC) is the destruction of portal bile ducts. Little information is available on apoptosis and cell proliferation in such bile ducts, so we used immunohistochemical techniques to locate molecules related to apoptosis [Fas antigen, Lewis Y antigen (BM1/JIMRO), and bcl-2 protein] and to cell proliferation (proliferating cell nuclear antigen, PCNA) in 21 patients with PBC. In addition, nick-end labelling was done to locate DNA fragmentation. The expression of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 34 publications
5
36
0
2
Order By: Relevance
“…It is intriguing to speculate that such heterogeneity may involve differential expression of FAS/APO-1 (CD95), the ''death receptor'' for apoptosis that is activated by FAS-ligand on CTL. 16 BEC expression of FAS/APO-1 has been identified in biopsies of patients with PBC 13,15 and normal human fetal liver. 51 In the latter, only some of the BEC expressed FAS/APO-1 in a given tissue section.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is intriguing to speculate that such heterogeneity may involve differential expression of FAS/APO-1 (CD95), the ''death receptor'' for apoptosis that is activated by FAS-ligand on CTL. 16 BEC expression of FAS/APO-1 has been identified in biopsies of patients with PBC 13,15 and normal human fetal liver. 51 In the latter, only some of the BEC expressed FAS/APO-1 in a given tissue section.…”
Section: Discussionmentioning
confidence: 99%
“…11 BEC in PBC also expressed costimulatory B7-1 (CD80), B7-2 (CD86), 14 and the apoptosis receptor, FAS/APO-1. 15 Collectively, these phenotypic changes indicate that BEC may be targets for either class I MHC-restricted CD8 or class II MHC-restricted CD4 CTL bearing FAS-ligand 16 and might function as ''professional'' antigen-presenting cells (APC). 17 However, the capacity to study the immunopathogenesis of NSDC and the immunologic function of isolated [18][19][20][21] or immortalized [22][23][24] human BEC remains limited.…”
mentioning
confidence: 99%
“…Ultimately, any model for PBC pathogenesis must be able to explain IBECs loss and the development of progressive ductopenia. Initial researches suggested that apoptosis was an important mechanism for IBECs loss in livers of PBC (Kuroki et al 1996;Harada et al 1997;Tinmouth et al 2002;Kawata et al 2012). Nevertheless, the apoptosis of IBECs is thought to be predominant in the middle groups male female Age (years) IL-17A (pg/ml) PBC 2 27 51.5 ± 14.2 2.63 ± 1.27 * Health control 2 9 46.9 ± 12.5 1.89 ± 0.52…”
Section: Discussionmentioning
confidence: 99%
“…Hydrophobic bile acids induce apoptosis in rat hepatocytes (Patel et al 1994). It is known that apoptotic changes occur in hepatocytes during primary biliary cirrhosis (Kuroki et al 1996).…”
Section: Discussionmentioning
confidence: 99%